THE EFFECT OF CONSUMER INTERESTS AND PRODUCT DIFFERENTIATION ON DAIHATSU CAR PURCHASE DECISIONS BRANCH OF PT. ASTRA MEDAN JOHOR - Syafi’i, Luqman; Firah, Al (Universitas Dharmawangsa Medan, 2023)
ABSTRACTÂ This research aims to research and analyze the influence of consumer tastes and product differentiation partially and simultaneously on Daihatsu car purchase decisions at PT.Astra International Tbk Branch of Johor Medan. The data analysis technique used is quantitative data analysis. The results of this study obtained a value of significance to consumer appetite based on the t test obtaining the size of thitung> ttable (7,478 >1,991) (Sig 0,023<Î±0,05) then H0 rejected means there is an influence of consumer taste on the purchase decision. The significance value of product differentiation based on the t test is obtained as thitung>table (2,236>1,991) (Sig 0,005<Î±0,05) then H0 is rejected means there is a significant influence of product diferenciation on the purchase decision. The result of the F test above is obtained Calculation > Ftable size (4,8473 > 3,11) (Sig 0,000 <Î±0,05) then H0 rejected means there is a significant influence of consumer tastes and product differentiation in Daihatsu car purchase decisions. The result of the regression is obtained that the Consumer Taste (X1) of 0.407 and Product Differentiation (X2) of 0.425 shows that the consumer taste and product differentiation variables have a positive and significant influence on the decision of purchase of Daihatsu Car in PT.Astra International Tbk Branch of Medan Johor means every increase in the variable of Consumer taste and product difference, then will have a negative impact on the purchase decision of the Daihatu Car in Pt.Â Keywords: consumer tastes, product differentiation, purchase decisions